Empirical Analysis of Internet Banking Adoption in Tunisia - Nasri, Wadie; Zarai, Mohamed (Asian Economic and Financial Review, 2014)
This paper aims to identify empirically the factors influencing the intention to use Internet Banking in Tunisia. The impact of perceived usefulness, perceived ease of use, awareness, social norm, security and privacy, and computer self efficacy on intention to use Internet banking is tested through structural equation modelling techniques. The 284 self-administrated questionnaires were collected from Tunisian’s customers who are using banking services in Tunisia. The findings of the study suggest that customer’ intention to use Internet banking can be affected by perceived usefulness and perceived ease of use of Internet banking. In turn, perceived usefulness can be affected by both perceived ease of use and influence social. Customers’ perceived ease of use can be determined by security and privacy and customers’ self-efficacy, and social influence. These findings may provide for banks useful guidelines for developing Internet banking systems in order to deliver services effectively.